Potentials and problems of internet as a source of purchasing information – experiences and attitudes of university students in Croatia - Knezevic, Blazenka; Jakovic, Bozidar; Strugar, Ivan (Business, Management and Economics Engineering, 2014)
Gathering information online prior to offline purchase became the common way of using Internet within student population. On the other hand, there are more and more Internet users and online shoppers at all Central European Countries. In the CEE region companies are searching the way how to approach students as a target group via their web sites. The purpose of this research was to explain (1) how student population in Croatia use Internet as a tool for gathering information on products and services and (2) to assess perceived problems and potential of Internet as a retail information source. The paper is based on a primary research – a survey on attitudes of Croatian students towards Internet and online shopping. Results are analyzed by using descriptive and inferential statistical method. Discussion of the results brings us to conclusions that there are statistically different attitudes among groups according to gender and according previous experience with the on-line shopping. For illustration: (a) males and females differ in assortment that they are choosing and buying online, (b) male students have a more positive attitude towards online shopping benefits than female students, and (c) online shoppers have more positive attitudes towards security issues than non-online shoppers.